Scaling Up Access to Electricity : Pay-as-You-Go Plans in Off-Grid Energy Services - Moreno, Alejandro; Bareisaite, Asta (World Bank, Washington, DC, 2015)
Although the payment models offered by off-grid energy companies are less flexible than those implemented with great success by mobile telephone companies, they may still have an important role to play in scaling up off-grid energy services for billions of people who lack access to electricity. More research is needed to assess the importance of flexible payments in attracting reliable low-income customers.